IMPLEMENTASI KELOMPOK USAHA BERSAMA "MAJU BERSAMA SATU" DALAM PENGURANGAN KEMISKINAN DI DESA SINGKALANYAR KECAMATAN PRAMBON KABUPATEN NGANJUK - Rakai Fatahillah Fahcrurokhim Al Baihaqqi; Ellya; Atirista (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
Joint Venture Group or Kelompok Usaha Bersama (KUBE) is an initiative by the Ministry of Social Affairs aimed at addressing poverty issues in Indonesia through a holistic approach. This research aims to evaluate the success of KUBE Maju Bersama 1 in poverty reduction, using a qualitative approach that focuses on social, institutional, and business development aspects. Qualitative methods are employed to understand the implementation of KUBE, with primary data obtained through in-depth interviews and observations, supplemented by secondary data from documentary studies. The selection of informants is done through purposive and accidental data, while the validity and reliability are assessed through data validity checks. This assessment includes degrees of trustworthiness, transferability, dependability, and confirmability. The research findings highlight strong interactions, a solid institutional structure, and sustainable business development as key factors in the success of KUBE. Consequently, programs like KUBE have the potential to have a significant positive impact on poverty reduction and the overall well-being of its members and the community. However, there is a need to enhance the capacity of managers and develop marketing strategies and empowerment beyond the core structure of KUBE Maju Bersama 1. This research provides insights into the importance of a holistic approach to poverty alleviation and encourages the enhancement of KUBE programs in Indonesia